TINDAK TUTUR DIREKTIF DALAM INTERAKSI BELAJAR MENGAJAR MATA PELAJARAN BAHASA INDONESIA DI MADRASAH ALIYAH NEGERI KOTABARU - Rudy Suryana (STKIP Paris Barantai, 2019)
Directive speech acts are an important aspect that is used in teaching and learning interactions. Therefore, it is important to pay attention to the use of directive speech acts spoken by teachers and students. This study aims to describe the types and functions of directive speech acts in teaching and learning interactions of Indonesian subjects class XI in Madrasah Aliyah Negeri Kotabaru. This research is a descriptive qualitative research. Data analysis using purposive sampling technique. Determination of the type and function of directive speech acts in the teaching and learning interactions of Indonesian subjects is based on indicators of the types and functions of directive speech acts derived from Chaer and Austin's theory. The results of research on teaching and learning interactions of Indonesian subjects in the Kotabaru Aliyah State Madrasah indicate that the use of the types of questions and the question asking function is more widely used, when compared to the use of other types and functions of directive speech acts. This can be seen in the description of the results of the study which shows that the type of questions with the asking function is more dominantly used with a number of 315 utterances out of a total of 826 directive utterances. Types of directive speech acts found include types of requests, questions, orders, prohibitions, licensing, advice. The directive speech act functions found include functions: asking, pleading, praying, asking, interrogating, instructing, wanting, demanding, directing, requiring, prohibiting, limiting, agreeing, granting, forgiving, condoning, allowing, suggesting, advising, asking and demanding, asking, demanding, directing, directing, requiring, prohibiting, limiting, agreeing, granting, forgiving, allowing, allowing, suggesting, advising, demanding, demanding, asking, demanding, directing, requiring, directing, requiring, prohibiting, limiting, agreeing, granting and direct, invite and pray, direct and ask, direct and demand, direct and advise, and finally allow and suggest. Keywords: Directive Speech Actions and Teaching and Learning Interactions